Experimental study on crashworthiness of empty/aluminum foam/honeycomb-filled CFRP tubes - Sun, Guangyong; Li, Shunfeng; Liu, Qiang; Li, Guangyao; Li, Qing (Composite structures, 2016)
Thin-walled structures have been more and more extensively used as energy absorbing components in industry. It however remains challenging to decide best possible structural configurations. This paper compares the crashworthiness of empty circular CFRP (Carbon Fiber Reinforced Plastics) with CFRP/aluminum/steel tubes filled with aluminum foam or aluminum honeycomb under axial quasi-static crushing. The effects of the following factors on crashworthiness are studied: length-to-diameter ratios (R=2, 3, 5) and ply numbers (5, 7, 9) of CFRP tube, the material of tube wall such as CFRP, aluminum and steel, the density of foam filler and the structural parameters of honeycomb filler. The experimental tests exhibit that all of empty circular CFRP specimens undergo a progressive end collapse subject to axial crushing. With the increase in R of CFRP tubes, both the energy absorption and loading capacities increase, with specific energy absorption (SEA) increasing from 48.60J/g to 60.37J/g. Most of the foam-filled tubes collapse in a progressive mode, exhibiting noticeable advantages in crashworthiness, attributable to the interaction between tubal wall and foam filler. Interestingly, the SEAs of foam-filled CFRP tubes are lower than that of the empty CFRP tube, while the SEAs of foam-filled metal tubes are higher than their empty counterparts. It is noted that in most cases, SEAs of the foam-filled CFRP tubes are higher than those of the metallic counterparts. The CFRP/aluminum/steel specimens filled with honeycomb also crushed in a more stable progressive manner, exhibiting certain advantages over the corresponding empty counterparts. Again, it is noted that the SEAs of CFRP tubes filled with honeycomb are slightly lower than the empty counterparts but far better than those of all metal specimens.